1999
DOI: 10.1111/j.1574-6968.1999.tb08784.x
|View full text |Cite
|
Sign up to set email alerts
|

Aeration affects acetate destination in Gibberella fujikuroi

Abstract: Gibberellins, fatty acids and the polyketides bikaverin and fusarin C are synthesized from a common precursor, acetyl-CoA. The production of these compounds in Gibberella fujikuroi was strongly influenced by aeration, determined by the air/medium ratio in shaken batch cultures. Higher aeration resulted in increased growth and the production of bikaverin and gibberellins. Low aeration stimulated fatty acid and fusarin C production. Feeding experiments with labeled leucine or acetate resulted in different propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…a Reference injection; b sample injection viscosity because of the short length of its mycelium and an increased gibberellin yield. Giordano and Domench [10] have described how oxygen availability causes differences in the biosynthesis of fats, pigments and gibberellins by G. fujikuroi. They reported that increased oxygen transfer increased the biosynthesis of gibberellins by G. fujikuroi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a Reference injection; b sample injection viscosity because of the short length of its mycelium and an increased gibberellin yield. Giordano and Domench [10] have described how oxygen availability causes differences in the biosynthesis of fats, pigments and gibberellins by G. fujikuroi. They reported that increased oxygen transfer increased the biosynthesis of gibberellins by G. fujikuroi.…”
Section: Discussionmentioning
confidence: 99%
“…Production of GA 3 by G. fujikuroi is strongly influenced by dissolved oxygen [10], the type of nitrogen source, the carbon source and the pH of the fermentation medium [6].…”
Section: Introductionmentioning
confidence: 99%
“…Of all environmental factors, the quality and quantity of the nitrogen source used in the growth media have a special effect not only on growth and differentiation, but also on the biosynthesis of many known fungal SMs, e.g., production of sterigmatocystin and aflatoxin in different Aspergillus species ( Chang et al, 1995 ; Feng and Leonard, 1998 ; Calvo et al, 2002 ; Ehrlich and Cotty, 2002 ), gibberellin (GA; Jefferys, 1970 ; Giordano and Domenech, 1999 ), fusarubin ( Studt et al, 2012 ), bikaverin ( Wiemann et al, 2009 ), fusaric acid ( Niehaus et al, 2014a ), and fusarin ( Díaz-Sánchez et al, 2012 ; Niehaus et al, 2013 ) in Fusarium fujikuroi , fumonisin in F. verticillioides ( Kim and Woloshuk, 2008 ), or cephalosporin, penicillin, and patulin in Acremonium chrysogenum , Penicillium chrysogenum , and P. urticae , respectively ( Rollins and Gaucher, 1994 ; Haas and Marzluf, 1995 ; Li et al, 2013 ). An overview of fungal SMs whose biosynthesis is affected by nitrogen availability is given in Table 1 .…”
Section: Regulation Of Secondary Metabolism By Nitrogen Availabilitymentioning
confidence: 99%
“…The optimal production was found at 30°C, a temperature above the optimal for growth [150]. In contrast to gibberellin and bikaverin production, fusarins are produced preferentially under low aeration [168].…”
Section: Relation Between the Synthesis Of Gibberellins And Polyketidesmentioning
confidence: 99%